Strategi Bimbingan Dan Konseling Dalam Mengembangkan Career Planning Siswa SMP - Hendri Ariyanti; Eklys Cheseda Makaria; Muhammad Arsyad (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Guidance and Counseling Strategies in Developing Career Planning for Junior High School Students Career planning is crucial for junior high school students, particularly those in the ninth grade who are transitioning to the next level of education. Many students still lack an understanding of their own potential, school options, and career paths that align with their interests and abilities. This study aims to describe Guidance and Counseling strategies for developing career planning among junior high school students. A qualitative approach with a phenomenological design was employed. The informants consisted of one guidance counselor and two ninth-grade students from SMP Negeri 6 Banjarmasin, selected via purposive sampling; data source triangulation involved subject teachers, homeroom teachers, and parents. Data collection techniques included interviews, observation, and documentation analysis. Data analysis utilized the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. The results indicate that Guidance and Counseling strategies were implemented through self-awareness activities, classroom guidance, group discussions, the use of profession-related videos and "career tree" media, collaboration with higher-level schools, and evaluation and follow-up. These services helped students better understand their interests, talents, abilities, aspirations, and suitable educational choices. The "career tree" served as a visual aid, helping students map the connections between their personal potential, school options, and career goals. The study concludes that Guidance and Counseling strategies play a vital role in helping students formulate career plans that are focused, realistic, and aligned with their personal potential. Future research is encouraged to involve a larger number of students, compare multiple schools, and develop a wider variety of career planning media to yield broader and more in-depth findings.